Cultural considerations in forgoing enteral feeding: A comparison between the Hong Kong Chinese, North American, and Malaysian Islamic patients with advanced dementia at the end-of-life - Ngan O.M.Y.; Bergstresser S.M.; Emdadul Haque A.T.M.; Chan H.Y.L.; Au D.K.S.; Suhaila Sanip (Blackwell Publishing Ltd, 2024)
Indexed by SCOPUS/ERA